Penatalaksanaan Elektrikal Stimulasi dan Mirror Exercise Fisioterapi pada Kasus Bells Palsy Sinistra di RSI Sunan Kudus - Ragil April Setianingrum (Journal of Health and Therapy, 2022)
Bell's palsy is a common neuropathy that causes weakness or paralysis of the facial nerve (the facial nerve). This condition causes the sufferer to have difficulty in moving half of the face consciously on the weak side. Symptoms of Bell's palsy occur in 20-30% of 100,000 people. This case report aims to present a physiotherapy management strategy in a case of Bell's Palsy. A 40-year-old woman with a medical diagnosis of Left Bell's Palsy. The patient complained of facial pain to the right and numbness and pain in the area behind the ear to the left neck. The physiotherapist met with the patient 8 times. Electrical stimulation can reduce the level and intensity of pain in the face that hurts, mirror exercise can improve facial functional status and increase self-confidence in patients is the benefit of physiotherapy management to solve the problem of bells palsy after 6 times therapy and evaluated. Physiotherapeutic interventions are very beneficial for patients with Bell's palsy. Although, the recovery process of peripheral nerves takes a long time, but with physiotherapy intervention can minimize the symptoms due to Bell's palsy. Further research is needed to determine the importance of physiotherapy in Bell's palsy. After physiotherapy intervention in the case of Bell's palsy 6 times using Electrical Stimulation and Mirror Exercise Therapy modalities, the results showed an increase in facial muscle strength, an increase in facial functional activity due to limitations of researchers, further research is needed to obtain an increase in functional activity in Bell's palsy patients.